(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to investigate implicature in Hollywood films. It is limited to different types of Hollywood films, namely: comic films and tragic films at three various selected periods: old period, middle period and modern period. The study consists of five sections : the preliminaries ( which presents the fundamentals of the study ) , the framework of the study ( which views the theoretical background on which the study is based ) , methodology and material ( which explains the basic procedures and the material that are used to conduct the study ) , the findings and discussion ( which displays the results of implicature in the selected scenes accompanied with discussion and examples ) and finally the conclusions which are drawn in the light of the findings.